Extraction and characterization of gelatin from bovine heart. (December 2017) - Roy, Bimol C.; Das, Chamali; Hong, Hui; Betti, Mirko; Bruce, Heather L.
Abstract: The objective of this study was to investigate the effects of initial heat extraction time and enzyme concentration during subsequent pepsin digestion on gelatin quality from bovine heart (BH) connective tissue (CT). BH gelatin was extracted from isolated BH CT at 80 °C for 4 or 6 h. Gelatin remaining in the CT residue was extracted with pepsin at either 100 or 200 mg pepsin/g CT to examine the yield and properties of enzyme-extracted gelatin. BH gelatins extracted at 80 °C showed very good gel strength (241–269 g) compared to that subsequently extracted with pepsin (54–96 g) and gelatin yield increased with the length of heat extraction (3%) although gel strength was reduced. Heat-extracted BH gelatin regardless of duration of heat extraction contained α1 and α2 chain as main components with some degradation peptides. The frequency sweep test of BH gelatins showed independency in a wide range of frequency (1–196 Hz) regardless of whether extracted by heat or pepsin. Heat-extracted BH gelatins exhibited the highest storage modulus values (1165–1245 pa). BH gelatins extracted with the lowest concentration of pepsin showed a higher mean storage modulus value than gelatin extracted with the highest pepsin concentration. The present study is the first to demonstrate that gelatin extracted from BH collagen using heat and pepsin has characteristics comparable to other sources of gelatin, making it suitable for many applications, and confirms that the use of pepsin increases BH gelatin yield with a concomitant reduction in gelatin quality. Graphical abstract: